THE EFFECT OF SUPERVISION, COMPENSATION SYSTEMS, AND ORGANIZATIONAL COMMITMENTS ON THE PERFORMANCE OF EMPLOYEES IN CONSTRUCTION SERVICES COMPANIES - Muhammad Djaelani; Sudja’i Sudja’i; Misbachul Munir; Didit Darmawan (ITB AAS INDONESIA Surakarta, 2021)
The construction industry involves many parties with various competencies and is related to the role of human resources in construction service companies. Human resource governance has contributed to the success and smooth operation of construction service companies. Human resources must be managed properly. Various management policy actions seek to utilize humans as a driver for the realization of organizational goals. Employee performance is an indication of the achievement of company goals. Supervision, compensation system, and organizational commitment are elements that affect employee performance. The purpose of this study was to determine the effect of supervision, compensation system, and organizational commitment on employee performance. The research was conducted in a construction service company in Surabaya involving 61 employees as respondents. The study used multiple linear regression analysis involving t test and F test as an analytical tool. The results of this study prove that partially and simultaneously the three independent variables have a significant effect on employee performance. Keywords : Supervision, Compensation System, Organizational Commitment, Employee Performance.